2016
DOI: 10.1039/c6ra02265k
|View full text |Cite
|
Sign up to set email alerts
|

Green alternative solvents for the copper-catalysed arylation of phenols and amides

Abstract: The use of alkyl acetates as green organic solvents for the Cu-catalysed arylation of phenols and amides is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 68 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…on the calculated reaction barrier values and the experimental reaction yields [7,14] we have found a direct relationship between both quantities, as can be seen in Figure 2. These findings emphasize the impact of substituent modifications in the Cu-lactam complex and the use of halogenated anilines.…”
Section: Energies and Reaction Profilessupporting
confidence: 62%
See 1 more Smart Citation
“…on the calculated reaction barrier values and the experimental reaction yields [7,14] we have found a direct relationship between both quantities, as can be seen in Figure 2. These findings emphasize the impact of substituent modifications in the Cu-lactam complex and the use of halogenated anilines.…”
Section: Energies and Reaction Profilessupporting
confidence: 62%
“…Consequently, a more comprehensive and rigorous analysis is imperative to attain a profound understanding of the underlying mechanisms and thereby facilitate informed and systematic enhancements in the process. Given the existence of multiple potential mechanisms for the Ullmann-Goldberg reaction [14][15][16][17][18][19][20][21][22][23], our study primarily focuses on investigating the catalytic cyclic pathway depicted in Scheme 2. The generally accepted mechanism for the Ullmann-Goldberg coupling reaction suggests that the CuI complex initially coordinates with the diamine ligand DMEDA (refer to Scheme 2, (I)).…”
Section: Introductionmentioning
confidence: 99%
“…Both these classes of compounds are listed as preferred solvents in solvent guides. 1176 , 1177 In particular, the latter type of solvents has been used in a variety of transition metal-catalysed reactions, 908 , 1178 1182 and EtOAc has for instance been demonstrated by Chang to be an effective replacement of DCE in a larger scale (200 mmol) C–H amidation protocol. 751 This will hopefully inspire further research in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…In the reaction of ArI, phenol is the product in the presence of CsOH, whereas an additional nonequivalent amount of Cs 2 CO 3 in same reaction gives diaryl ether . Recently, Sambiagio et al . reported that an electron‐withdrawing group on picolinamide ligands (acetates as solvents) increases the efficiency of the catalytic system.…”
Section: Introductionmentioning
confidence: 99%